2018
DOI: 10.1002/ejlt.201800017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Oxidative Stability of Cold‐Pressed Rapeseed Oil by Rancimat and Pressure Differential Scanning Calorimetry Measurements

Abstract: Cold‐pressed market rapeseed oils are evaluated for oxidative stability using two accelerated methods: Rancimat and pressure differential scanning calorimetry. In the study, oils are also determined by their acid, peroxide and p‐anisidine values, fatty acid composition, antioxidants capacity, and phenolic compounds content. Obtained results of oxidative stability are correlated to determine the possibility of using interchangeably tested methods. To examine the impact of individual quality factors on oil oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Symoniuk et al . () concludes that there is no high correlation between the tocopherol content and oxidative stability in the Rancimat apparatus. In addition, many less strong or weak linear statistically significant relationships have been demonstrated.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Symoniuk et al . () concludes that there is no high correlation between the tocopherol content and oxidative stability in the Rancimat apparatus. In addition, many less strong or weak linear statistically significant relationships have been demonstrated.…”
Section: Resultsmentioning
confidence: 95%
“…Low R 2 indicate a poor fit of the model of the effect of ozonation time on the induction time. The autoxidation process is influenced by the content of fatty acids and the location and type of bonds present therein, as well as the qualitative and quantitative composition of the antioxidant groups contained in the oil (Symoniuk et al ., ). In the studied oils, oxidative stability primarily depended on the cultivar, but statistical analysis showed that ozonation also caused changes in this parameter.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations